Synthetic multispecies microbial communities reveals shifts in secondary metabolism and facilitates cryptic natural product discovery. (14th August 2017) - Shi, Yutong; Pan, Chengqian; Wang, Kuiwu; Chen, Xuegang; Wu, Xiaodan; Chen, Chen‐Tung Arthur; Wu, Bin
Summary: Chemically mediated interactions have been hypothesized to be essential for ecosystem functioning as co‐occurring organisms can influence the performance of each other by metabolic means. Here, we present a co‐culture device that allows co‐culturing of microorganisms that are physically separated but can exchange chemical signals and metabolites. This setup was adopted to perform investigations on the secondary metabolisms of both a fungal–bacterial community and an actinomycetic–actinomycetic community. This study employed a metabolomics approach integrating LC‐MS profiling, multivariate data analysis and molecular networking techniques. LC‐MS measurements revealed a pronounced influence of such chemical communication on the metabolic profiles of synthetic co‐culture communities with a group of molecules being induced or upregulated in co‐cultures. A novel antibiotic exhibiting antibiotic properties against Klebsiella pneumoniae was unveiled in the fungal–bacterial community. Besides, a further survey of the fungal–bacterial cross‐talk indicated that the production of co‐culture‐induced diphenyl ethers by fungi might result from the fungal response against the secretion of surfactins by bacteria in the cross‐talk. This study demonstrated that the presented co‐culture device and the metabolomic routine would facilitate the investigation on chemically mediated interactions in nature as well as cryptic natural products discovery.